КЛИНИЧЕСКИЕ ОСОБЕННОСТИ ГИПЕРПЛАСТИЧЕСКИХ ПРОЦЕССОВ ПРИ АМК В ПЕРИМЕНОПАУЗАЛЬНОМ ПЕРИОДЕ У ЖЕНЩИН С ОЖИРЕНИЕМ (Лучшие интеллектуальные исследования, 2025)
Резюме: Аномальное маточное кровотечение (АМК) является частой встречаемой патологией у женщин в перименопаузе [2,4].  Оно определяется как маточное кровотечение, при котором продолжительность, частота или объем кровотечения считаются чрезмерными и негативно влияют на качество жизни (КЖ) и психологическое благополучие женщин. У женщин данного возраста обычно отмечается увеличение веса вследствие чего её качества жизни и сексуальной активность страдает, а это в первую очередь связано с гормональными изменениями [1,3,5]. В данной статье мы провели ретроспективный анализ женщин перименопаузального периода с жалобами на аномальное маточное кровотечение для определения влияния лишнего веса на возникновение кровотечения в данном возрасте. Ключевые слова: перименопауза, морофологические признаки, аномальное маточное кровотечение.Resume: Abnormal uterine bleeding (AUB) is a common pathology in perimenopausal women [2,4]. It is defined as uterine bleeding in which the duration, frequency, or volume of bleeding is considered excessive and adversely affects a woman's quality of life (QoL) and psychological well-being. In women of this age, weight gain is usually noted, as a result of which her quality of life and sexual activity suffer, and this is primarily due to hormonal changes [1,3,5].  In this article, we conducted a retrospective analysis of perimenopausal women with complaints of abnormal uterine bleeding to determine the impact of excess weight on the occurrence of bleeding at this age.Resume: Abnormal uterine bleeding (AUB) is a common pathology in perimenopausal women [2,4]. It is defined as uterine bleeding in which the duration, frequency, or volume of bleeding is considered excessive and adversely affects a woman's quality of life (QoL) and psychological well-being. In women of this age, weight gain is usually noted, as a result of which her quality of life and sexual activity suffer, and this is primarily due to hormonal changes [1,3,5].  In this article, we conducted a retrospective analysis of perimenopausal women with complaints of abnormal uterine bleeding to determine the impact of excess weight on the occurrence of bleeding at this age.